Human trafficking and migrant smuggling in Southeast Europe and Russia: learning criminal entrepreneurship and traditional culture - Leman, Johan (Transnational crime, crime control and security, 2015)
Networks: rational and cultural components -- Leadership and structures: the discovery of the impact of learning -- Making the business operational -- Increasing benefits, decreasing risks -- "Money, money, money... always sunny!" -- Rational and cultural: conclusions and policy proposals